Group approach in aids prevention: analysis of knowledge of young people from Fortaleza - Thiago Moura de Araújo; Neiva Francenely Cunha Vieira; Márcio Flávio Moura de Araújo; Patrícia Neyva da Costa Pinheiro (Rev Rene)
The objective of this work was to analyze adolescents’ knowledge about AIDS in Civil Social Organizations (OSC) which adopted the referential of groups in Fortaleza-Ceará. 24 youngsters of both sexes were accompanied during three meetings. They were between 13 and 24 years old and were from two groups linked to the organizations. The participant observation and the application of a structured questionnaire were used for the data collection. We identified that a good amount of adolescents has knowledge about AIDS and its means of prevention, however there are still doubts about the transmition of the HIV. The TV was the most mentioned source of information about AIDS (91,6%), followed by the school (87,5%) and friends (75%). Dialog about sexuality with parents occurred sometimes in 50% of the researched, while only 12,5% always talked about it. We conclude that the group approach is a praiseworthy source for health education of adolescents in the context of Aids, since it promotes knowledge with more dynamism.